PENGARUH METODE DISKUSI TERHADAP KETERAMPILAN KOMUNIKASI SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK NEGERI 3 KOTA BEKASI - Kasmiati Devi; Irham Irham (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2021)
This study aims to determine the effect of discussion methods on students’ communication skills.The method used in this research is an experimental research method with a Quasi-Experimentalmethod, with a Nonequivalent Control Group design which is a form of quasi-experimental or quasiexperimentalresearch methods. This study involved two classes, namely the experimental class andthe control class. Where the experimental class and the control class get the same learning in termsof assignments, content, teaching materials and learning time. The difference is in the treatmentgiven. The experimental class received teaching and learning treatment using the discussion method,while the control class used the lecture method. Data collection in the form of questionnaires anddocumentation. The sample used in this study amounted to 64 students. Where 32 students for theexperimental class and 32 students for the control class. he results of the study were shown by analyzingthe data using the formula “Paired sampe t-test”, then the results showed that t count> t table (9.976> 2.0395) with a significance level of 5%. And the resulting post-test mean score of the experimentalclass is 84.56 and the post-test mean score of the control class is 80.25. So, the post-test mean scoreof the experimental class is greater than the post-test mean score. -test control class. So the proposedhypothesis has been proven that the Discussion Method has an Influence on Student CommunicationSkills. This shows that the use of the discussion method has a positive effect on student communicationskills in Islamic education learning at SMK Negeri 3 Bekasi City.